When dad and mom are away from home... Panji Paniba 11.20-45 - Molen, Willem van der (UI Scholars Hub, 2021)
Access to the pre-modern world of Classical Javanese literature (seventeenth- nineteenth centuries) starts with a sound knowledge of its idiom. “When dad and mom are away from home...” leads the novice through grammatical constructions and vocabulary not found in Modern Javanese literature. The light-hearted story providing these examples is taken from the Panji Paniba. This early nineteenth-century text belongs to a famous group of Javanese romances of chivalry going by the name of “Panji stories”, all set in the Hindu era of the East-Javanese kingdom of Kediri.